Digitalisasi Literasi dan Penerimaan Digitalisasi dalam Pelayanan Kesehatan - Sulyaprilawati Battri Siahaan; Marice Simarmata (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The digital transformation of healthcare services in rural areas necessitates the equitable enhancement of digital literacy among village officials and healthcare workers. This study was conducted in Dayeuhkolot Village, Subang Regency, using a quantitative approach and a comparative experimental design to evaluate the effectiveness of traditional lecture-based training versus hands-on computer tutorial training. A total of 24 purposively selected participants, consisting of village officials and community service agents, were involved. The results indicate that hands-on training is significantly more effective in improving digital understanding and skills, as reflected in higher post-test scores and a narrower range of participant results. Age and educational background were found to be pivotal in shaping digital readiness, with younger and more educated individuals adapting more swiftly to new technologies. These findings underscore the necessity for adaptive and inclusive digital training as a foundational element for the digital transformation of healthcare services in rural communities.